The relationship between infertility and psychological factors, depression and anxiety: A review study - Nikojoyerad, Atefeh; Aghajani , Tahmores; Bonakdari , Nasrin (Researcher Bulletin of Medical Sciences, 2022)
Objective: Infertility has always been a common problem in various human societies. Today, the infertility rate is going to rise and a large percentage of couples have infertility problems in the world. Awareness of infertility and long-term treatment affect people's mental health. The main purpose of this study was to investigate the effects of depression on infertility. This study was conducted by reviewing method. To select the content used, first the topics found by the search engine were examined in terms of thematic correlation, and then the obtained content was divided. Using the keywords depression, infertility, and women, it was done from the science direct database, avid, google scholar, pubmed, and 80 articles were obtained, of which 10 were selected for review. A review of findings from infertility studies inside and outside Iran suggests ways to reduce infertility and treat depression, including cognitive-behavioral therapy (CBT) and co-medication, which can help prevent sexual dysfunction and depression, which is effective in treating depression in these patients. Therefore, due to the effects of high depression, especially its effect on ovulation, it is recommended to consider the treatment of depression, which is emphasized in people who are undergoing infertility treatment, to reduce the impact of depression on the treatment process.